ANÁLISE DA VIABILIDADE ECONÔMICA DE AÇÕES DE CONSERVAÇÃO DE ÁGUA EM UM CAMPUS UNIVERSITÁRIO - Pacheco, Gabriela Cristina Ribeiro; Campos, Marcus Andre Siqueira; Vaz, Fernando Henrique Brito; Martins, Gustavo Arantes (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The drinking water shortage evidences this resouce conservation need. As domestic use represents a significant part of water used in the world, to optimize consumption and reduces the supply of water for domestic uses becomes a priority for reducing the water consumed. So, this work seeks to analyze the consumption and verify the feasibility of some actions for water conservation in a university campus. In this way, it was conducted a diagnosis of water supply through the survey of consumption of buildings and an existing losses prevision. With this analysis, four actions were proposed to reduce water consumption, including: repair of leakages visible or not; use of sanitary equipment that consumes smaller water volume and rainwater harvesting. Finally, for each proposed intervention financial indicators were calculated and it was verified that all the options present an environmental benefit with the saved water and are financially feasible, therefore, they could be set up in the university campus.